Integrated model‐driven engineering of blockchain applications for business processes and asset management. (9th November 2020) - Lu, Qinghua; Binh Tran, An; Weber, Ingo; O'Connor, Hugo; Rimba, Paul; Xu, Xiwei; Staples, Mark; Zhu, Liming; Jeffery, Ross
Abstract: Blockchain has attracted broad interests to build decentralised applications. A typical class of applications uses blockchain for the management of cross‐organisational business processes as well as assets. However, developing such applications without introducing vulnerabilities is hard for developers, not the least because the deployed code is immutable and can be called by anyone with access to the network. Model‐driven engineering (MDE) helps to reduce those risks, by combining proven code snippets as per the model specification, which is easier to understand than source code. Therefore, in this article, we present an approach for integrated MDE across business processes and asset management (e.g., for settlement). Our approach includes methods for fungible/non‐fungible asset registration, escrow for conditional payment, and asset swap. The proposed MDE approach is implemented in a smart contract generation tool called Lorikeet, and evaluated in terms of feasibility, functional correctness, and cost effectiveness.